Project Management Application Design, Tasks and Collaboration in Improving Employee Performance - Afrina; Endi, Alzaidi; Wahyudiono, Pratiwi Hendro (Journal of Engineering, Technology, and Applied Science (JETAS), 2022)
Perkembangan sistem informasi manajemen telah menyebabkan terjadinya perubahan yang signifikan dalam pola pengambilan keputusan yang dilakukan oleh manajemen pada tingkat operasional dan pimpinan. Penelitian ini bertujuan untuk merancang dan mengimplementasikan Aplikasi Manajemen Proyek, Tugas dan Kolaborasi Dalam Meningkatkan Kinerja Pegawai yang diharapkan dapat bermanfaat untuk membantu dalam mengatur dan mengontrol sebuah proyek pengembangan perangkat lunak di TIK BP Batam sehingga proyek yang dikerjakan dapat berjalan dengan baik dan selesai tepat waktu serta dapat meningkatkan kinerja pegawai TIK BP Batam. Project Management Application Design, Tasks and Collaboration in Improving Employee Performance Abstract: The development of management information systems has led to significant changes in the pattern of decision making by management at the operational and leadership levels. This study aims to design and implement Project Management Applications, Tasks and Collaboration in Improving Employee Performance which is expected to be useful for assisting in managing and controlling a software development project at ICT BP Batam so that the projects carried out can run well and be completed on time and can improve the performance of ICT BP Batam employees. Keywords: Information System, Project Management Application, Increasing Performance.